Empowerment Of Sweet Potato Farmers In Cilembu Village, Pamulihan District, Sumedang Regency, West Java Province - Richal Johry Salenda; Fernandes Simangunsong; Gatiningsih Gatiningsih (Sean Institute, 2025)
The government is required to play an active role in encouraging the implementation of Community Empowerment so that the powerlessness can finally be empowered, especially for farmers and sweet potato farmer groups in Cilembu Village, Pamulihan District, where the goal is for independence to be realized for farmers in making a living. The purpose of this study was to determine and analyze the supporting and inhibiting factors of Sweet Potato Farmer Community Empowerment in Cilembu Village, as well as to determine and analyze efforts to overcome the inhibiting factors of Sweet Potato Farmer Community Empowerment in Cilembu Village, Pamulihan District, Sumedang Regency, West Java Province. The method used is a qualitative approach with data collection techniques, namely interviews, observation and documentation. The data analysis technique in this study with several stages, namely data reduction, data presentation, and conclusions. Based on the results of field research, it can be seen that community empowerment for sweet potato farmer groups in Cilembu Village has not been maximized, due to various things that researchers have found in the field, namely: Minimal and lack of agricultural extension human resources, lack of implementation of routine agricultural Technical Guidance from upstream to downstream, especially understanding in reading climate and weather that always changes every season and farmers' understanding of the market, land problems and water limitations in farming Sweet Potatoes in Cilembu Village, there are no regulations governing the characteristics of Cilembu sweet potatoes and standardization of prices in the market, the role of Corporate institutions and Asaguci has not been maximized, lack of farmer regeneration for Cilembu sweet potato commodities. limited agricultural infrastructure, and the need for the role of technology and research in the field of Cilembu sweet potato agriculture in a sustainable and sustainable manner.